Analisa Teknologi Informasi dalam Mekanisme Pemasangan Iklan Sebagai Jaminan Pendapatan dengan Pendekatan Teori Computational Advertising (Studi Kasus Detikcom) - Taufik Rendi Anggara; Suhardi (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2013)
Internet is one of media of communication with the very rapid development. In Online Advertising company based in particular on Contextual Advertising for revenue assurance (Revenue Assurance) is higher than ever needs to be analyzed in depth theoretical approach is also relevant in order to get results and to solve problems.